Pharmacognostic And Phytochemical Evaluation Of Cordia Obliqua Willd Fruits: Pharmaceutical Science-Pharmacognosy - Tharun Babu, G; Sivakrishnan, S; Sharma, Jvc (International Journal of Life Science and Pharma Research, 2022)
Cordia (family Boraginaceae) is a genus of deciduous flowering trees or shrubs comprising more than 300 species distributed widely in the tropical regions. The aim of this research was to provide scientific information on phramacognostical nature and presence of various phytochemicals in the fruits of Cordia obliqua. The present study helped to evaluate anatomical, histochemical, physico chemical analysis and chemical tests of various extracts of Cordia obliqua willd fruits. Common names of plants are “Naruvili, Ali and Namaviri (Tamil), Lassura Viri, Cheruvari (Kerala). China-nakeru (Andhra and Telangana)”. It is considered as one of the most important medicinal plants and various plant parts like leaves, fruits, bark and seed were found to possess abundant ethno medicinal value. Most frequently they are used to treat many ailments such as respiratory disorders, stomach pain, wound, inflammation, myalgia, cough, dysentery and diarrhoea. The fruits are widely used for the treatment of spleen and hepatic disorders. The anatomical and histochemical characteristics of the fruits of Cordia obliqua have been studied which helped in authentication and diagnose the various anatomical characters like presence of epidermis, mucilage, xylem and phloem fibers and calcium oxalate crystals. Proximate analyses of fruits were performed which included moisture content, extractive values and ash values helped to identify the purity and solubility of fruits in different solvents which was revealed by extractive values. Chemical tests helped to know the various phytoconstituents present in the fruits of Cordia obliqua when tested with various chemical reagents. Phytochemical tests revealed the presence of steroids, glycosides, alkaloids, tannins, phenolic and flavonoid compounds and carbohydrates.